Factors Related to Household Waste Water Channels (SPAL) in the Working Area of the Sanggaran Agung Community Health Center, Kerinci Regency in 2023 - Andy Amir; Ameliza Qamara Dinda; Fitria Eka Putri; Dwi Noerjoedianto; Oka Lesmana S (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2023)
Sewerage is a drain used to dispose and collect waste water from bathrooms, washing places, kitchens (not from latrines). Data from the Kerinci District Health Office shows that the percentage of SPAL ownership in the working area of the Sanggaran Agung Health Center is 76.20%. This study aims to determine factors related to the management of household wastewater sewerage (SPAL) in the working area of the Sanggaran Agung Health Center, Kerinci Regency in 2023. This type of research is Quantitative with Cross Sectional approach. The sampling technique uses the Proportionate Stratified Random Sampling Technique with a sampling of 104 households. The study instrument used questionnaires and observation sheets. The analysis of this study used univariate and biavariate analysis with chi square test. The results of the analysis showed that 66.3% of respondents did not meet the SPAL requirements and there was a relationship between education (P-Value = 0.002), Knowledge (P-Value = 0.000), Attitude (P-Value = 0.000) towards household wastewater sewerage management (SPAL) in the working area of the Sanggaran Agung Health Center.